17beta-estradiol and testosterone influence the mRNA expression and the time course of inflammatory cytokines in activated human monocytic cell line (THP-1) - C. Craviotto; A. Sulli; P. Montagna; B. Villaggio; S. Capellino; M. Cutolo (PAGEPress Publications, 2011)
Objective: The aim of this study was to evaluate the effects of 17b-estradiol (E2) and testosterone (T) on the mRNA expression of IL-1b, IL-6, TNF-a and TGF-b in cultured human monocytic cells (THP-1) after INF-g activation. Methods: THP-1 were cultured with E2 and T (10 nM) for 24 hs and then activated with INF-g (500 U/ml), during different periods of time (1, 3, 6, and 12 hs). After total RNA extraction, all samples were analyzed by multiple RT-PCR to detect mRNA expression of the selected cytokines. Results: Cells cultured without hormonal treatment expressed IL-1b mRNA after 1 h; on the contrary TNF-a, TGF-b and IL-6 mRNA were expressed only after 3 hs. At 6 and 12 hs only IL-6 mRNA was still expressed. Interestingly, cells cultured with testosterone never expressed IL-1b nor TNF-a mRNA and showed an IL-6 mRNA expression similar to the untreated controls at 3, 6 and 12 hours. On the contrary, cells treated with E2 showed the expression of all cytokines at 3 and 12 hs, and in general showed an higher expression of all the analyzed cytokines mRNA when compared to the other conditions. Conclusions: This study suggests that sex hormones may modulate the cytokine mRNA expression in the inflammatory cells. In fact, T inhibits TNF-a production at all the tested times, whereas E2 seems to accelerate and to enhance the inflammatory response. Therefore, the altered sex hormone ratio, as observed in the synovial fluid of RA patients (high E2/low T), might contribute to the occurrence and last of synovitis.